Holistic Pedagogical Strategies in Islamic Education in Reducing the Negative Impacts of Online Games on Students’ Character - Meysi Salsahbilla; Benny Prasetya; Muhammad Alfi Syahrin; Khamam Khosiin (PT. Caesarindo Triloka Persada, 2026)
The development of online games among secondary school students has become a phenomenon that is inseparable from adolescent life and carries serious implications for character formation, particularly learning discipline, self-control, and religious character. Uncontrolled intensity of online game use has the potential to shift students’ priorities from academic and spiritual activities toward instant entertainment-oriented activities. This study aims to analyze holistic pedagogical strategies in Islamic education in reducing the negative impacts of online games on students’ character. The research employed a descriptive qualitative approach, with research subjects consisting of the school principal, Islamic Education teachers, Guidance and Counseling teachers, and students at SMA Negeri 5 Berau. Data were collected through in-depth interviews, observation, and documentation, while data analysis used the interactive model of Miles and Huberman. The results indicate that online games have an impact on declining learning discipline, weakened self-control, and reduced consistency of students’ worship practices. Nevertheless, the implementation of holistic pedagogical strategies that integrate spiritual, emotional, social, and pedagogical development through the role of Islamic Education teachers as mu’allim, murabbi, muaddib, counselors, and mediators has proven capable of helping students manage online game use more wisely and strengthen religious character. This study affirms that holistic pedagogy in Islamic education has a strategic role in addressing the challenges of student character formation in the digital era.